2006
DOI: 10.1016/j.jvs.2006.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gene polymorphisms in ulcer healing process after superficial venous surgery

Abstract: The FXIII-34L variant was significantly associated with shorter healing time after superficial venous surgery, suggesting a role in the healing and tissue regeneration phases. Conversely, HFE-C282Y, despite its role in ulcer establishment, did not affect the postoperative healing time. In perspective, the identification of patients with a poor prognosis may give clinicians the opportunity to modify management and to target tailored therapies in the view of a new and alternative concept of treatment based on ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 37 publications
0
59
0
1
Order By: Relevance
“…In addition, chronic skin lesions were negatively associated with FXIII activity and with L34-allele (7). Finally, other FXIII gene variants responsible for increased molecule activity were associated with better prognosis and shorter healing time after surgery (8,47). Considering that VV34-carriers have a basal mean FXIII activity of about 70%-90% (7,33,this paper) and that after acute MI, a reduction of circulating FXIII begins (37,this paper), VV34-patients might be disadvantaged in recovering myocardial functions respective to L34-carriers with significantly higher activity (7,33,this paper).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, chronic skin lesions were negatively associated with FXIII activity and with L34-allele (7). Finally, other FXIII gene variants responsible for increased molecule activity were associated with better prognosis and shorter healing time after surgery (8,47). Considering that VV34-carriers have a basal mean FXIII activity of about 70%-90% (7,33,this paper) and that after acute MI, a reduction of circulating FXIII begins (37,this paper), VV34-patients might be disadvantaged in recovering myocardial functions respective to L34-carriers with significantly higher activity (7,33,this paper).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, carrier patients with chronic vascular insufficiency and venous leg ulcer had a significantly shorter mean healing time of the skin lesion after venous reflux correction. This happened despite the fact that the elective vascular surgery intervention was completely successful in all treated patients (8). Reper-fusion treatment by percutaneous coronary intervention (PCI) is the most efficacious and utilized medical strategy in acute MI (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the FXIII-A 34L variant displays improved crosslinking activity towards extracellular matrix components, thus further augmenting the antifibrinolytic properties of FXIII. Consequently, this modification should result in enhanced fibroblast migration followed by significantly improved ulcer healing (72)(73)(74). Indeed, these suggestions were confirmed by Gemmati et al (72) and Tognazzo et al (73), who found that 34LL homozygous patients displayed a 2-fold higher FXIII activity at the same FXIII blood level compared to wild-type 34VV homozygotous ones.…”
Section: Cvu Healing-promoting Variantsmentioning
confidence: 78%
“…In contrast to the previously described CVU formation-inducing polymorphisms, variants of certain genes also facilitate wound healing. Among these is a polymorphism concerned with a gene encoding for coagulation factor XIII (FXIII) subunit A (72)(73)(74).…”
Section: Cvu Healing-promoting Variantsmentioning
confidence: 99%
“…Specific Factor XIII genotypes have favorable ulcer healing rates, while the HFE gene mutation, despite its importance in venous ulcer risk, has no influence on healing time. 22 …”
Section: Genetic Influencesmentioning
confidence: 99%